CHALLENGES AND ISSUES IN BIG DATA - Krithika, M.Meena; Parameswari, K.Kannika; Gayathri, K. (IJRDO -Journal of Computer Science Engineering, 2016)
The espouse of data-driven determination making is being conceived broadly, and there is enlarging excitement for the idea of "Big Data". While the espouse of Big Data is genuine, there is parallel gap within its potentiality and its attainment. Heterogeneity, complexity, timeliness, progress, and recession problems with Big Data prevent proceeding at all stages of the pipeline that can produce value from data. The obstacle starts instantly during data appropriation, when the data obligate us to make determination currently in an ad hoc manner. Most of the data is not related in structured format. The assessment of data blow up when it can be combined with another data, thus data adherence is a greater creator of evaluation. Since many data is instantaneously originated in digital format today and we have the scope and denounce to persuade the creation to propitiate subsequently and to automatically link previously completed data. Data analysis, association, gathering and modeling are other basic challenges. Data analysis is a open bottleneck in several applications, both due to requirement of scalability of the domestic algorithms and due to the complication of the data that needs to be resolved. The many unique challenges and opportunities comparable with Big Data involve rethinking several outlooks of these data management stages, while maintaining other beneficial aspects. We conclude that particular investment in Big Data will lead to a new wave of fundamental technological growth that will be embodied in the next origination of Big data management and analysis platform. We conclude that these research issues are not only instant, but also have the ability to create large economic value in the economy for years to come. However, they are also difficult and requiring us to rethink data analysis systems in crucial ways. A dominant investment in Big data, efficiently directed, can flow not only in major scientific advances, but also lay the footing for the next origination of advances in medicine, science, and business.